The Impact of the Reality Show “Clash of Champions” on the Learning Motivation of International Special Class Students (KKI) FTIK UINSI Samarinda - Muhammad Nurhadi Setyawan; Shafa Shafa; Atika Muliyandari (Fakultas Tarbiyah dan Ilmu Keguruan UIN Sultan Aji Muhammad Idris Samarinda, 2025)
This research is motivated by the rapid development of digital media that indirectly affects the world of education, especially through platforms such as YouTube. One of the educational shows that attracts attention is the Clash of Champions reality show produced by Ruangguru. This reality show carries the concept of competition between outstanding students from various well-known campuses, which is packaged in an inspiring and entertaining format. This type of show is relatively new and rare, but it has managed to attract the interest of many students, including university students. This reality show not only presents intellectual competition, but also emphasizes values such as the spirit of learning, teamwork, and perseverance. Thus, the purpose of this study is to determine the impact of the reality show “clash of champions” on the motivation of students of the International Special Class (KKI) FTIK UINSI Samarinda